Political economy of agricultural protectionism in the EU and US - Saraç, Esin. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
Until the Uruguay Round, agriculture was an exceptional issue in international trade talks. However, at the end of the Uruguay Round, the agricultural sector was brought under the WTO disciplines. The proponents of the Agreement argued that it would introduce the fundamental reforms necessary for agricultural trade liberalization. However, the implementation process showed that this was not going to be the case for the future of the sector. On the contrary, protectionist policies in world agricultural markets continued because the Agreement contained some loopholes through which the WTO members could preserve their domestic agricultural supports and continue to restrict access to their agricultural markets while claiming to fulfill their obligations under the Agreement. In this sense, the agricultural policies of two major players in global agricultural trade, the European Union and the United States, were crucial because they were the leading WTO members who influenced the negotiation process and shaped the final agreement. Therefore, in my thesis within the framework of Robert Putnam̕s two-level game approach, I examined the questions of why and how the EU and the US have continued to protect their agricultural sectors. Under the interaction of the pressures at Level I negotiations and the restrictions of the dynamics at Level II (and Level III for the EU) - institutional constraints and the pressure of domestic agricultural interests - the EU and the US followed certain complementary strategies through which they have continued their protectionist agricultural policies.
Keywords: Protectionism.; Tariff on farm produce.; Export subsidies.; Produce trade -- United States.; International cooperation.